Remote Working and Human Resources Management in the Post-pandemic Reality: A qualitative Research of Entrepreneurs and Employees in Poland - Małgorzata REMBIASZ; Paulina SIEMIENIAK (Communications of International Proceedings, 2024)
The article presents selected aspects of remote working during the COVID-19 pandemic and prospects for the future development of this form of working. The article presents the results of two studies. The first one concerned the impact of the COVID-19 pandemic and remote working on the professional and personal lives of young women and men. The second one was conducted among 350 small and medium-sized Polish enterprises. The results were compared with reports and other studies. In the first study, amongst the respondents (regardless of gender) it was noted that the pandemic led to an increased amount of time devoted to personal life with the simultaneous lowering of work motivation and poor work efficiency. Despite more leisure time, young women, like men, did not want to continue working remotely. The overwhelming majority of the entrepreneurs surveyed believe that the mental well-being of employees is an important issue and that employers should include it in their human resource management strategies. Respondents also tended to agree with the statement that working parents should have the right to greater flexibility in the hours and form of their work than other employees. The reflections and research findings are a contribution to the study of the socio-economic consequences of the pandemic and the post-pandemic reality.
Keywords: remote working; COVID-19; human resources management; the SME sector